A inseparabilidade das questões de fato e de direito e o modelo de processo civil cooperativo - Lanes, Júlio Cesar Goulart (2013)
By making use of the guidelines in the cooperative civil lawsuit model, the thesis proposed herein is meant to show that points of fact and points of law are inseparable. As we acknowledge that the theory of law and especially the theory of interpretation influence jurisdiction, we need to go back to understand how the problem of dealing with the case's factual-legal elements has evolved. Under the cognitive theory of legal interpretation, also known as formalist, which recognizes the radical separation between fact and law, we are going to study the following schools of legal reasoning: the School of Exegesis, the Jurisprudence of Concepts, the Historic School of Law, the School of Free Law, the Jurisprudence of Interests, and Legal Topics. Alternatively, along the lines of the skeptical theory, also called antiformalist, whether from its logic-argumentative side or for the contribution from philosophical hermeneutics, we find that we should not assume the isolation and the absence of reciprocal implication between fact and right in the process of interpreting and applying the Law. Based on the results found, we are going to transfer and apply the same dialectics between the cognitive and skeptical theories to address the following lawsuit issues: the right to sue, right to evidence, and right to state reasons, all of them inherent to properly putting together a civil lawsuit. Especially from that confrontation we realize that points of fact and points of law are inseparable, which helps put together the case and cooperatively reach its fair decision.